Adsorptive removal of azithromycin antibiotic from aqueous solution by KOH-modified rice husk biochar. - Gomez, Ashley June M.
Since the onset of the COVID-19 pandemic, there have been concerns expressed about the potential adverse effects of increased antibiotic consumption. Azithromycin (AZM), a type of macrolide antibiotic, has gained prominence due to its potential as a therapeutic treatment for COVID-19 infection. A recent study indicates a significant increase in the pollution of azithromycin, particularly in hospital effluents. The synthesis of KOH-modified rice husk biochar (KRHBC) was conducted to remove AZM from an aqueous solution. The inclusion of KOH significantly improved the formation of a more porous structure and facilitated the integration of various surface functional groups, as verified using SEM and FTIR studies, respectively. The point of zero charge (pHpzc) of the KRHBC was determined to be around 9.56. The two-level full factorial design experiment revealed that parameters such as solution pH, adsorbent dosage, initial AZM concentration substantially impacted the removal of AZM. The highest AZM removal efficiency (80.5%) was achieved by using a solution of pH of 9.0, an adsorbent dosage of 0.01 g, and an initial AZM concentration of 10 ppm. The model was validated at 95% confidence level by achieving an actual removal efficiency of 84.0% under the desired operating parameters. The pseudo-first-order kinetic model evidently represented the adsorption kinetics (with R2 of 0.97872). Meanwhile, the Redlich-Peterson model (with R2 of 0.9792) provided the best fit in the investigation of AZM adsorption isotherms. The results suggest that the adsorption of AZM is on a heterogeneous adsorbent surface and is mainly governed by physisorption. The AZM adsorption may involve several mechanisms, including â„¼-â„¼ interaction, electrostatic attraction, and hydrogen bonding. The accumulated findings indicate that KRHBC is a very efficient adsorbent for eliminating developing pollutants, such as azithromycin, from aqueous solution.